Skiing simulation based on skill-guided motion planning - Hu, C. H.; Lee, C. Y.; Liou, Y. T.; Sung, F. Y.; Lin, W. C. (Computer Graphics Forum, 2019)
Skiing is a popular recreational sport, and competitive skiing has been events at the Winter Olympic Games. Due to its wide moving range in the outdoor environment, motion capture of skiing is hard and usually not a good solution for generating skiing animations. Physical simulation offers a more viable alternative. However, skiing simulation is challenging as skiing involves many complicated motor skills and physics, such as balance keeping, movement coordination, articulated body dynamics and ski-snow reaction. In particular, as no reference motions — usually from MOCAP data — are readily available for guiding the high-level motor control, we need to synthesize plausible reference motions additionally. To solve this problem, sports techniques are exploited for reference motion planning. We propose a physics-based framework that employs kinetic analyses of skiing techniques and the ski-snow contact model to generate realistic skiing motions.